Improvement of growth and development of sweet basil (Ocimum basilicum L.) through the application of chitosan at different plant maturity stages - Qazizadah, Ahmad Zubair; Nakasha, Jaafar Juju; Sinniah, Uma Rani; Megat Wahab, Puteri Edaroyati (Universiti Putra Malaysia Press, 2023)
Sweet basil is one of the most popular culinary, medicinal, and fragrance herbs in Mediterranean, Asian, and Western countries. This study aims to increase the growth performance of sweet basil via different concentrations of chitosan, which is applied at three growth stages. The study was arranged in a factorial randomized complete block design with four replications. The plants were divided into three growth stages, which were the vegetative stage (S1), the reproductive stage (S2), and both the vegetative and reproductive stages (S1 + S2). Those plants were then treated with four different concentrations of chitosan (0, 2, 4, and 6 ml/L) either on S1, S2, or S1 + S2. The results indicated that plants treated with chitosan at S1 showed greater performance. Chitosan concentration of 4 ml/L produced greater plant height (55.09 ± 1.75 cm/plant), stem diameter (11.08 ± 0.89 mm/plant), and a number of leaves (296.57 ± 11.61 leaves/plant). It is also interesting to observe that the lowest chitosan concentration was non-significantly different, with 4 ml/L at S1 in some parameters. Plants in those treatments showed the highest average length of internode, number of branches, total root length, average root diameter, total root volume, and total root surface area. Besides, correlation analysis proved that all the parameters significantly correlated positively. As the concentration of 4 ml/L showed a superior effect, especially on the number of yields, thus it is recommended for growers to apply chitosan at 4 ml/L during S1.